EVALUATION OF FINANCIAL PERFORMANCES OF SME’S LISTED IN THE BIST SME INDUSTRIAL INDEX BY USING TOPSIS MULTICRITERIA DECISION MAKING METHOD - Kendirli, Selcuk; Kaya, Muhammet Selcuk; Bilgin, Mustafa (Journal of Economic Development, Environment and People, 2020)
In this study, the financial performances of SMEs listed in the BIST SME Industrial Index are evaluated by using TOPSIS multicriteria decision-making method. The data of the study acquired from annual financial statements that reported between the 2016-2018 period. Financial performance ranks of SMEs are determined for each year and thus comparative financial performances of SMEs are detected. BIST SME Industrial Index is an index that includes stocks of industrial SMEs traded in BIST Stars, BIST Main, and BIST Emerging Companies markets. SMEs have great importance for the Turkish economy, with their dynamizing roles and with their crucial roles in regional development and job creation. According to the Turkey Statistical Institute data, Turkish SMEs constitute 99.8 % of all enterprises in Turkey. At the same time, Turkish SMEs provide 72.7% of total employment, 62% of total sales, and 58% of the total investments of the Turkish Economy. Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is one of the multicriteria decision-making methods that commonly used in the evaluation of financial performances of firms. The TOPSIS method is based on two main points: the positive ideal solution and the negative ideal solution. With the help of the TOPSIS method, the distances positive ideal solutions and negative ideal solutions of all options are calculated. Options are ranked according to their proximity to the positive ideal solution and their distance to the negative ideal solution.